Learning-based local visual representation and indexing - Rongrong, Ji; Yao, Hongxun; Gao, Yao; Dai, Qionghai (Amsterdam : Morgan Kaufmann, 2014)
Learning-Based Local Visual Representation and Indexing, reviews the state-of-the-art in visual content representation and indexing, introduces cutting-edge techniques in learning based visual representation, and discusses emerging topics in visual local representation, and introduces the most recent advances in content-based visual search techniques.
CIP data; resource not viewed.
Includes bibliographical references.
Keywords: Computer vision; Pattern recognition systems; COMPUTERS -- General; Computer vision; Pattern recognition systems; Electronic books